An Error Analysis And The Impact Of Contingent Teaching In Solving Problems Involving Measures Of Dispersion - Ng, Chiew Leng (2023)
The importance of statistical learning has been widely discussed. However, little effort has been made to understand the difficulties of students in learning measure of dispersion, which is the key component to statistical learning. Employing multiphase mixed method, the present was divided into three phases. The first phase which involved 85 high school students using cluster sampling was sought to first examine and categorize the kinds of errors students committed in solving problems involving measures of dispersion. Subsequently, in depth interviews based on the model of contingent teaching were carried out in the second phase with ten low performing students in order to understand the reasons why students have the errors in solving problems involving measures of dispersion. In the third phase, this study focused on determining if there is a significant difference in the achievement of the students in solving problems regarding measures of dispersion before and after going through contingent teaching. The findings indicated that students committed errors in solving problems related to measure of dispersion due to lacking statistical vocabulary knowledge, weak symbol sense, rote learning, low statistical reasoning and statistical thinking ability. This study revealed that contingent teaching is effective (